Design My Future: An Instrument to Assess Future Orientation and Resilience. (May 2017) - Santilli, Sara; Ginevra, Maria C.; Sgaramella, Teresa M.; Nota, Laura; Ferrari, Lea; Soresi, Salvatore
This article reports the development and psychometric requisites of Design My Future, an instrument assessing future orientation and resilience. Three different studies involving Italian preadolescents were conducted. With the first, the items were developed and the factor structure verified; the second confirmed instrument's multidimensional structure and evaluated its discriminant validity. The third study was conducted to verify the invariance of factorial structure across gender. Results provide strong psychometric support for Design My Future as a valid measure for analyzing middle school students' thoughts about their future orientation and resilience and for career education and career counseling activities.